Analysis and Identification of Work Posture to Complaints of Musculoskeletal Disorders (MSDs) with REBA Method (Case Study at CV. Sumber Sari, Jember Regency) - Rusdianto, Andrew Setiawan; Mahardika, Nidya Shara; Suryaningrat, Ida Bagus; Nuriah, Santi; Hartanti, Ragil Ismi (International Journal on Food, Agriculture and Natural Resources, 2023)
This study discusses the analysis of work posture on all activities of workers who produce coco fiber in CV. Sumber Sari is located in Lembengan Village, Jember Regency. The production processes that are currently operating are the jockey, drying, sieving, and pressing processes. Work activities are carried out repeatedly, causing complaints to workers. These complaints arise due to non-ergonomic posture causing pain in several parts of the body felt by workers. The purpose of this study was to determine the level of risk and the percentage of complaints experienced during the production process. The methods used are the Standard Nordic Questionnaire (SNQ) and the Rapid Entire Body Assessment (REBA). The results of the research from the SNQ questionnaire on the manufacture of coco fiber, the body segments of workers mostly experience complaints on the back, waist and thighs. Research using the REBA method has a very high level of risk in jockey, sieving, and pressing workers (A4 and A5).Keywords— musculoskeletal disorders, working posture, SNQ, REBA